Баллистика стрельбы - Янченко, О. О. (ХНУРЕ, 2019)
Ballistics in the game is carried out by two productions: 1) visual; 2) mechanical. When creating a shooting in a visual way, objects are used (for example, a sphere). In this case, standard physics shoots Unity3D, which does not allow fast because of speed, and flies through various other objects about high speeds. Because of this problem, developers use the second method. The way out of this situation, the proposed script with which the shooting becomes more realistic. This script should answer the following questions: How is the shooting? Is there a collision? How is the calculation of the damage coefficient